СНИЖЕНИЕ ВОЗДЕЙСТВИЯ КИСЛОРОДА НА ЖИДКИЙ МЕТАЛЛ ЭЛЕКТРОДОВ ПРИ ЭЛЕКТРОДУГОВОМ НАПЫЛЕНИИ ПУЛЬСИРУЮЩЕЙ РАСПЫЛЯЮЩЕЙ СТРУЕЙ ВОЗДУХА - Роянов Вячеслав Александрович; Захарова Ирина Вячеславовна; Крючков Никита Сергеевич; Пугачев Евгений Витальевич (World Science, 2019)
In electric arc metallization an intensive oxidation of the spraying metal takes place due to the oxygen contained in the air which causes a great reduction in contents of alloying elements in the coating. In order to reduce the oxidizing impact of the air-spraying jet on the liquid metal of electrodes a method involving pulsing air feed has been developed. This is achieved by introducing an additional element into the spraying head of an electric arc metallizer. The analytical dependencies presented in this paper are to determine the level of reduction of air consumption in electric arc spraying as well as the reduction in the mass of oxygen in contact with the air. There have been represented some examples of chemical composition of coatings when air consumption is dropped by 35-40% which diminishes the energy give-out on its reproduction.